2016
DOI: 10.1902/jop.2015.140638
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Parathyroid Hormone May Augment Bone Volume in Autogenous Grafts: A Study in Rats

Abstract: Systemic administration of PTH(1-34) augmented bone volume in autogenous grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Many animal studies have found PTH to be effective in not only long bones,(Jahng & Kim, ; Kakar et al, ; Kim & Jahng, ) but also calvarial defect models(Andreassen & Cacciafesta, ; dos Santos et al, ; Sheyn et al, ) and the mandible. (Tang et al, ) Takahata, Awad, O'Keefe, Bukata, and Schwarz () reviewed that PTH was effective in both endochondral and intramembranous bone healing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many animal studies have found PTH to be effective in not only long bones,(Jahng & Kim, ; Kakar et al, ; Kim & Jahng, ) but also calvarial defect models(Andreassen & Cacciafesta, ; dos Santos et al, ; Sheyn et al, ) and the mandible. (Tang et al, ) Takahata, Awad, O'Keefe, Bukata, and Schwarz () reviewed that PTH was effective in both endochondral and intramembranous bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…Many animal studies have found PTH to be effective in not only long bones, (Jahng & Kim, 2000;Kakar et al, 2007;Kim & Jahng, 1999) but also calvarial defect models (Andreassen & Cacciafesta, 2004;dos Santos et al, 2016;Sheyn et al, 2013) and the mandible. However, several studies have shown that teriparatide may have different effects on different skeletal sites (Iida-Klein et al, 2002;Lindsay et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other animal studies, PTH stimulated distraction osteogenesis in rabbits [ 18 ] and allograft integration in calvarial bone defects in mice [ 19 ]. Animal studies related to dental effects found that PTH stimulated healing after bone graft on extraction sockets [ 20 ] and calvarial bone autografts on the mandible in rats [ 21 ]. However, studies of the effect of PTH on bone grafts are still deficient, and PTH has not been evaluated previously in sinus augmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies that were mentioned above, it is expected that intermittent PTH could stimulate the bone regeneration after maxillary sinus augmentation. Several studies performed in maxillofacial region of rabbit or rat showed especially that PTH increased jaw mineral density in rabbit [ 29 ], increased volume of calvarial autograft on mandible in rat [ 21 ], and increased bone fill of graft on extraction socket in rat [ 20 ]. These might support our hypothesis.…”
Section: Introductionmentioning
confidence: 99%